Pengaruh Penggunaan Media Kartu Huruf Bergambar Terhadap Kemampuan Membaca Permulaan Pada Siswa Kelas 1 SDN 067093 Cinta Damai - Nainggolan, Maria Friska; Sinaga, Arman Bemby; Shalihat, Hilma Mitalia; Tambunan, Ruth Grace (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2022)
The purpose of this study is to determine the effect of flash card on early reading skills of first grade students at SDN 067093 Cinta Damai in academic year of 2021/2022. This research is Pre-Experimental Design. The research was conducted in October - November 2022. The sample used was 22 students which was total of the population. The data collection techniques used in this research were test, documentation and observation. The results of this study indicate that there was an effect of flash card on early reading skills of first grade students at SDN 067093 Cinta Damai. It can be proven from the results of the analysis by using t-test, showing that t count > t table , 10,864 > 1.411, then Ho is rejected and Ha is accepted. It can be conclude that there is an effect of flash card on early reading ability of first grade students at SDN 067093 Cinta Damai.